2021
DOI: 10.1186/s43141-021-00228-w
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis of silver nanoparticles with algae and the importance of capping agents in the process

Abstract: Background Nanoparticle synthesis is a very interesting area of research currently due to the wide applications of nanoparticles. The nanoparticles have a diameter ranging between 1 and 100 nm and they are used in different fields like electronics, pharmaceuticals, cosmetics, biotechnology, medicines, etc. Main body of the abstract Nanoparticles have gained the interest of researchers due to their large surface-to-volume ratio and their capability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
56
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(75 citation statements)
references
References 143 publications
1
56
0
Order By: Relevance
“…Wound healing: Wound dressing is usually required for the maintenance of the environment, eliminating the growth of other invading microorganisms, and the removal of excess fluid and dead cells around the wound. To overcome the problems (narrow antimicrobial spectrum, skin allergies, irritation, and cytotoxicity) related to the use of conventional drugs [glucocorticoid steroids and nonsteroid anti-inflammatory drugs (ibuprofen, naproxen, diclofenac, ketoprofen, indomethacin, and acetylsalicylic acid)], various types of metallic nanoparticles have been used in the healing process (Chugh et al, 2021). It has been found that silver, zinc oxide, and gold nanoparticles coated with biomolecules like polysaccharides and biological extracts help in the wound healing mechanism.…”
Section: Biomedical Applications Of Capped Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Wound healing: Wound dressing is usually required for the maintenance of the environment, eliminating the growth of other invading microorganisms, and the removal of excess fluid and dead cells around the wound. To overcome the problems (narrow antimicrobial spectrum, skin allergies, irritation, and cytotoxicity) related to the use of conventional drugs [glucocorticoid steroids and nonsteroid anti-inflammatory drugs (ibuprofen, naproxen, diclofenac, ketoprofen, indomethacin, and acetylsalicylic acid)], various types of metallic nanoparticles have been used in the healing process (Chugh et al, 2021). It has been found that silver, zinc oxide, and gold nanoparticles coated with biomolecules like polysaccharides and biological extracts help in the wound healing mechanism.…”
Section: Biomedical Applications Of Capped Nanoparticlesmentioning
confidence: 99%
“…It has been found that silver, zinc oxide, and gold nanoparticles coated with biomolecules like polysaccharides and biological extracts help in the wound healing mechanism. These nanoparticles trigger apoptosis, tissue necrosis, platelet and stem cell activation, angiogenesis, tissue scar formation, and bacterial clearance and reduce cytokines (IL-6 and IL-10) and reepithelialization (Wang et al, 2017;Ovais et al, 2018;Batool et al, 2021;Chugh et al, 2021).…”
Section: Biomedical Applications Of Capped Nanoparticlesmentioning
confidence: 99%
“…Recent advances in the field of nanotechnology have influenced and increased the use of silverbased compounds at a nanometer size. Several physical and chemical methods have been reported for the synthesis of AgNPs [4,5], however, AgNPs produced by these methods lead to the production of noxious compounds that are toxic to cells and the environment. To overcome these toxic effects, green synthesis methods, using natural products as reducing and stabilizing agents, were developed [6].…”
Section: Introductionmentioning
confidence: 99%
“…The use of plant extracts in green synthesis is easier, more efficient, eco-friendly and incurs low cost in comparison with the chemical or microbial mediated synthesis methods. Plant materials are cost-effective as plants are renewable, readily available, and contain antioxidant-rich phytochemicals [4] that can play a major role in the reduction and stabilization of Ag + into bioactive AgNPs. The availability of plants makes the green method amenable to large-scale production of NPs.…”
Section: Introductionmentioning
confidence: 99%
“…However, physical and chemical methods involve high energy constraints and the use of toxic reagents for synthesis. This issue can be overcome by employing biological agents, such as bacteria, fungi, algae, actinomycetes, and plants for the synthesis of metal nanoparticles (John et al 2021 ; Koul et al 2021 ; Chugh et al 2021 ; Rai et al 2021 ; Dikshit et al 2021 ). Recently, the use of plant extracts for nanoparticle synthesis has received much attention due to the rich diversity of phytochemicals, availability in bulk quantities, and simplicity (Balciunaitiene et al 2021 ; Amjad et al 2021 ; Gaddam et al 2021 ; Aboyewa et al 2021 ; Selvakesavan and Franklin 2021 ; Sawalha et al 2021 ; Rajagopal et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%